2003
DOI: 10.1128/iai.71.12.6962-6970.2003
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the Mycobacterium tuberculosis MprAB Two-Component SignalTransductionSystem

Abstract: The mechanisms utilized by Mycobacterium tuberculosis to establish, maintain, or reactivate from latent infection in the host are largely unknown but likely include genes that mediate adaptation to conditions encountered during persistence. Previously, a two-component signal transduction system, mprAB, was found to be required in M. tuberculosis for establishment and maintenance of persistent infection in a tissue-and stage-specific fashion. To begin to characterize the role of this system in M. tuberculosis p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
71
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 43 publications
(51 reference statements)
4
71
0
Order By: Relevance
“…TCSs are histidine phosphotransfer systems involved in sensing environmental changes and triggering adaptive responses (Hoch & Varughese, 2001). Studies indicate that MprA is an autoregulatory transcription factor, which is phosphorylated by the histidine kinase MprB (He & Zahrt, 2005;Zahrt et al, 2003). Results of genome-wide transposon mutagenesis suggested that mprB was essential for growth in broth, whereas mprA was nonessential (Sassetti et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TCSs are histidine phosphotransfer systems involved in sensing environmental changes and triggering adaptive responses (Hoch & Varughese, 2001). Studies indicate that MprA is an autoregulatory transcription factor, which is phosphorylated by the histidine kinase MprB (He & Zahrt, 2005;Zahrt et al, 2003). Results of genome-wide transposon mutagenesis suggested that mprB was essential for growth in broth, whereas mprA was nonessential (Sassetti et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…TCSs are histidine phosphotransfer systems involved in sensing environmental changes and triggering adaptive responses (Hoch & Varughese, 2001). Studies indicate that MprA is an autoregulatory transcription factor, which is phosphorylated by the histidine kinase MprB (He & Zahrt, 2005;Zahrt et al, 2003). …”
mentioning
confidence: 99%
“…Of these, only the mtrA-mtrB system is essential (Via et al ., 1996;Zahrt and Deretic, 2000;Parish et al ., 2003a), while others are required under specific growth conditions, namely, mprA-B for maintenance of persistence (Zahrt and Deretic, 2001), devR-S for regulation of hypoxic response (Sherman et al ., 2001;Park et al ., 2003) and prrA-B for intramacrophage growth (Ewann et al ., 2002;. Deletion of regX-sensX , dev R, pho P-R and prrA-B and kdpD-kdp E affects growth and virulence in animal infection models (Perez et al ., 2001;Parish et al ., 2003a,b;Sassetti and Rubin, 2003;Zahrt et al ., 2003;Malhotra et al ., 2004;Roberts et al ., 2004;Tyagi and Sharma, 2004;Asensio et al ., 2006). The functional roles played by many of these response regulators, and the environmental signals they respond to, are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…These systems use transient phosphorylation of the sensory and regulatory proteins at conserved residues for transducing extracellular or intracellular signals, thereby leading to an appropriate cellular response [2]. Such phosphorylation-based signalling has been established for five of eleven systems in M. tuberculosis, RegX3-SenX3 [3], TrcR-TrcS [4], MprA-MprB [5], PrrA-PrrB [6] and DevR-DevS (Rv3133c-Rv3132c/DosR-DosS) [7]. The genes encoding two-component systems are generally located adjacent to each other and are also coexpressed.…”
Section: Introductionmentioning
confidence: 99%